Preparation and realization of compact touring exhibitions on the example of exhibition projects of the Masaryk University - Pavol Tišliar (Muzeológia a Kultúrne Dedičstvo, 2023)
The article focuses on the specifics of the preparation and realization of compact touring exhibition projects. In the introductory theoretical part, it deals with the issue of museum communication and museum presentation, their means, approaches and forms, on the basis of which several types of exhibition projects are distinguished. Special attention is paid to touring exhibitions, their specifics and possibilities in relation to the public. In the empirical part, the article contains several examples of the preparation and realization of compact touring exhibition projects, implemented in the field of Museology at the Masaryk University in Brno.